Antibacterial lipid liquid crystalline nanoparticles – synthesis and optimization by central composite design - Jakub Jagielski; Karolina Dydak; Kaja Jaskot; Dmytro Soloviov; Maciej Kozak; Grzegorz Nowaczyk (Artificial Cells, Nanomedicine, and Biotechnology)
The rise of antibiotic-resistant bacteria demands new antimicrobial strategies. Glyceryl monolaurate (GML) shows antibacterial activity against Gram-positive bacteria like S. aureus but is ineffective against Gram-negative E. coli due to its outer membrane. GML’s limited solubility and susceptibility to bacterial lipases hinder its direct use. This study developed glyceryl monooleate (GMO) lipid liquid crystalline nanoparticles (LLCNPs) incorporating GML to enhance its stability and efficacy. Using a central composite design (CCD), an optimal GMO:GML:F127 mass ratio of 26.5:3.5:1.5 was achieved. Characterization via dynamic light scattering (DLS), small angle X-ray scattering (SAXS), and cryo-transmission electron microscopy (cryo-TEM) confirmed the formation of bicontinuous cubic phase nanoparticles (Pn3m space group) with hydrophobic, hydrophilic, and amphiphilic regions, enabling the incorporation of diverse agents and the presence of sponge-like nanoparticles. The optimized LLCNPs inhibited S. aureus growth at concentrations ≥10 µg/mL by disrupting its membrane potential but showed no activity against E. coli. Cytotoxicity studies indicated that GML incorporation did not significantly affect cell viability compared to pure GMO LLCNPs. This nanoparticle system offers a biocompatible solution for treating Gram-positive bacterial infections and may synergize with existing antibiotics, warranting further investigation into its mechanisms and therapeutic potential.